Screen-printed advanced all-solid-state symmetric supercapacitor using activated carbon on flexible nickel foam. (September 2022) - Tu, Qian; Li, Xianran; Xiong, Zeyu; Wang, Hongxia; Fu, Jun; Chen, Liangzhe
Abstract: There is an urgent demand to develop an all-solid-state flexible supercapacitor for portable digital products, screen printing technology is deemed a valid way. However, it still faces challenges including the use of printed substrate and low specific capacitance caused by printing. In this paper, a new route for the fabrication of advanced all-solid-state symmetric supercapacitors (SSC) via screen-printing is demonstrated. The mesoporous activated carbon (AC) inks are prepared to fabricate electrodes, while their performances as well as the printing parameter i.e. stencil meshes are investigated carefully. Surprisingly, the optimal screen-printed electrode shows an enhanced specific capacitance (159.0 F/g at a current density of 1 A/g with a retention rate of 98.2 % after 5000 cycles at 10 A/g) than that of electrodes made by the smearing method (139.8 F/g with a retention rate of 76.1 %). This improvement can be ascribed to the orderly aligned activated carbon after the shearing interaction in the process of screen-printing. Furthermore, flexible and porous nickel foam is served as a printed substrate and current collector, and the SSC with an interdigital pattern is assembled coating with KOH/PVA gel electrolyte, which can deliver a remarkable areal energy density of 64.8 μWh/cm 2 at a power density of 0.2 mW/cm 2 . Notably, a red lamp (2.5 V) can be lightened up by SSC in series and sustained for more than 300 s. Therefore, this paper paves a new way for the facile fabrication of screen-printed energy storage devices. Graphical abstract: Unlabelled Image Highlights: Employment of nickel as the printing substrate and current collector for all-solid-state symmetrical supercapacitor (SSC). The SSC enables deliver a significant areal energy density of 64.8 μWh/cm 2 at a power density of 0.2 mW/cm 2 . A red light (2.5 V) can be lighten up by three SSCs in series for more than 5 minutes in practical applications.